Form and Type of Familum in The Tuber Family - Adelia Putri; Aura Alfisyahrin; Diah Khairani; Lusia Selvina Br Hutabarat; Tri Mustika Sarjani (Jurnal Biologi Tropis, 2023)
Starch is a type of polysaccharide formed from the polymerization of glucose. Starch is also known as starch which is a widespread reserve polysaccharide in plants. Starch is also defined as a complex carbohydrate which is very important as a food source. The purpose of this research is to determine the shape and type of starch in the tuber family. This research was conducted using descriptive methods. The purpose of this study is to describe and describe the characteristics of the forms and types of starch.Based on the results of observations, it can be concluded that the starch in taro, cassava, porang and jicama tubers has a concentric type and has regular and irregular round shapes, while potato tubers have an eccentric type and are oval or oblong in shape.Potato tubers have the highest starch of the five tubers because potatoes have a dense starch structure and contain a lot of starch or starch.